Governare la città Pratiche sociali e linguaggi politici a Genova in età medievale - Giovanna Petti Balbi (Reti Medievali E-Book, 2007)
The social and political organization and the power culture of an important medieval city-state constitute the glue of the essays recollected here. The approach to the history of Genoa concerns different aspects, which lie outside from the mere small town reality, with raids on the territory especially in Riviera di levante. It is a history of enterprising men, which project in different directions their own ambitions and their desire to achievement. The homely strategies, the social dynamic, the language of institutio and society come together to outline the unsettled orders of Genoa which tries, unsuccessfully, to come in the fifteenth century to government and representation forms similar to ones completed in others Italian spheres.